Development of lightweight ultra high performance concrete to architectural applications. - Xilotl-Dominguez, Jorge; Durán-Herrera, Alejandro; Lopez Yepez, Lucio Guillermo; Muñoz Espinoza, Ana Luisa (Revista ALCONPAT, 2025)
This study aims to reduce the weight and enhance the thermal performance of Ultra-High-Performance Concrete (UHPC) for architectural applications while maintaining adequate mechanical strength. To achieve this, expanded polystyrene perlite (EPP) was used to replace limestone sand by mass (0, 30, 55, 80, and 100%) and synthetic Polyvinyl Alcohol (PVA) structural fiber was added. The mixes were evaluated for compressive and flexural strength, surface and bulk electrical resistivity, and thermal conductivity. Results showed that EPP significantly reduced density and thermal conductivity, while PVA improved strength. However, high EPP contents decreased mechanical performance. The combination of EPP and PVA in UHPC is innovative. It was concluded that optimized mixtures can balance thermal efficiency and structural integrity for architectural uses.